Analysis of the Legislative Description of Thefts Committed in Various Ways - Nataliy Sergeevna Tretyakova (Сибирское юридическое обозрение, 2011)
This article discusses how to describe the various forms of theft. The article notes that the law they are write differently. The author proposes to come to some uniformity to reflect the legislative definitions of accessory to theft.